Durability Performance of Geopolymer Concrete: A Review - Wong L.S. (MDPI, 2023)
Abrasion; Acid resistance; Alkalinity; Aluminosilicates; Chemical bonds; Chlorine compounds; Compressive strength; Concretes; Construction industry; Erosion; Fly ash; Geopolymers; Inorganic polymers; Polypropylenes; Portland cement; Silica; Acid attack; Alkaline activators; Aluminosilicate source; Chloride ion penetrability; Chloride ions; Durability performance; Geopolymer concrete; Geopolymerization; Ordinary Portland cement; Portland cement concretes; Durability